Γ-limit for a sharp interface model related to pattern formation on biomembranes - Brazke, Denis; Knüpfer, Hans; Marciniak-Czochra, Anna (Arxiv, 2022)
We derive a macroscopic limit for a sharp interface version of a model proposed in [29] to investigate pattern formation due to competition of chemical and mechanical forces in biomembranes. We identify sub- and supercrital parameter regimes and show with the introduction of the autocorrelation function that the ground state energy leads to the isoperimetric problem in the subcritical regime, which is interpreted to not form fine scale patterns.
Gesehen am 17.10.2022